PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONCEPT SENTENCE DAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MATA PELAJARAN EKONOMI PADA SMA NEGERI 3 KOTA JAMBI - Lili Andriani, Lepi Candra (Universitas Batanghari Jambi, 2017)
This study aims to find out student learning outcomes using the concept model of learning sentence, knowing student learning outcomes using scramble learning model, knowing differences in student learning outcomes using the concept model of learning sentence and scramble on the economic subjects of class XI SMA Negeri 3 Kota Jambi.The result of the research shows that the result of the students 'learning in the control class at the initial and second pre test no students reach KKM, nor the result of the students' learning in the experimental class on the initial pre test and secondly there are no students who reach KKM. There were about 40 students, while there were 25 students who did not graduate from KKM (62,50%), and only 15 students graduated from KKM (37,50%). At the post-test in the experimental class students who did not pass as many as 13 students (43.33%), and 17 students who passed the KKM (56.67%). This means that the post test value in the control class is smaller than the experimental class. Thus, it can be concluded that the learning model of scramble can help students more focused in learning and can improve student learning outcomes.Kata Kunci : Model Pembelajaran, Concept Sentence, Scramble